Economic viability analysis of the use of a pump operating as a turbine operating at variable frequency as an alternative to generate electricity compared to rural electrification in the state of Minas Gerais (Research, Society and Development, 2018)
The distributed generation is the generation close to the consuming load, has the advantage to reduce losses in power distribution, independent of the power, taking advantage of the local energy potential. In this context, the study addresses the use of pump and turbine - PAT for power generation and this is done with the use of water resources, by cheap, accessible and easy configuration. In the methodology the paper shows the viability like power generator working in variable frequency, tracing its best range of operation. The results show satisfactory yields, utilizing the local energy potential, promoting energy efficiency, democratization of energy due to its configuration and cost, accessible to isolated and poor communities. In addition, a comparison of cost technology with rural electrification is carried out.